Ornament, fantasy, and desire in nineteenth-century French literature - Gordon, Rae Beth, 1940- (Princeton legacy library., 1992)
In this examination of the role of ornament in nineteenth-century French literature, Rae Beth Gordon shows that ornament, far from being a simple accessory, raises problems that are at the very heart of aesthetic experience: limits and their transgression, illusion and seduction, pleasure and tension, harmony and confusion, excess and marginality. After placing texts by Nerval, Gautier, Mallarm, Huysmans, and Rachilde within the context of the history and techniques of the decorative arts, she reveals in these works the powerful role played by decorative figurations of syntax, diction, and composition. Gordon's detailed textual analyses yield spatial parallels with specific ornamental configurations (interlace, arabesque, decorative frame, horror vacui, trompe l'oeil). These patterns are then studied in relation to a dynamics of desire. Ornament, taken as the site of desire and illuminated by the theories of Charcot, Clrambault, Freud, Winnicott, and Lacan, highlights important differences between romanticism, symbolism, and decadence. Not only does the author relate ornament to artistic representations of the sublime, the grotesque, and hysteria, but she also reveals that the function of ornament in literature anticipated psychiatric and aesthetic research on decorative form in the fin de sicle. Originally published in 1992. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.